The optimal size of German cities: An efficiency analysis perspective - Stephan Hitzschke (Technische Universität Darmstadt, Department of Law and Economics, 2011)
This work investigates the interrelation between production efficiency and population size of German cities. The productive efficiency in this context is the scale efficiency, which is a result of positive and negative agglomeration externalities. The investigation is performed in a two-stage process. First, the efficiency in terms of scale efficiency is measured using nonparametric methods. The second stage investigates the relation of scale efficiency and populations size. It turns out that the optimal city size in Germany is about 220,000 inhabitants, which is almost the mean size of all German cities involved. Although there are regional differences, optimal city size remains stable as the mean size.
Keywords: D24; O47; R12; R15; 330; Efficiency analysis; optimal city size; population size; German cities; Stadtgröße; Stadtbevölkerung; Technische Effizienz; Skalenertrag; Agglomerationseffekt; Schätzung; Deutschland